Catalyst for phthalate hydrogenation as well as preparation method and application thereof
By using a modified support and coated Fe in the catalyst, combining Ru and Fe as active components, the problem of poor loss and stability of the catalyst in the fixed drip bed reactor is solved, and high activity and high selection are achieved Catalyst preparation with long-term stability.
Patent Information
- Application Number
- CN202310714601.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-15
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-06-15
AI Technical Summary
In the prior art, when the catalyst is run for a long time in a fixed drip bed reactor, the noble metal Ru loss rate is high, the catalyst stability is poor, and it is difficult to achieve catalyst preparation with high activity, high selectivity and long-term stability.
Using a catalyst containing a primary catalyst precursor and Fe coated on its surface, a modified support is formed by heat treatment of thin aluminite and TiO2, and modulation is made by specific metal oxides, combining Ru and Fe as active components, A bimetallic structure is formed to improve the activity and stability of the catalyst.
The catalyst has achieved high activity, high selectivity and good stability, and the loss rate of precious metal Ru is reduced. After long-term use, the DINP conversion and DINCH selectivity of the catalyst are both above 95%, and the loss rate of precious metal Ru does not exceed 0.04ppm%. .
Smart Images

Figure CN119158592A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalysts, and in particular to a catalyst for hydrogenation of phthalates, a preparation method and application thereof, and a method for preparing diisononyl cyclohexane 1,2-dicarboxylate from diisononyl phthalate. Background Art
[0002] Plasticizers, also known as plasticizers, are a type of polymer material auxiliary agent. The most common plasticizers are phthalates. Phthalates, as plasticizers widely used in children's toys, medical devices, food packaging, etc., have always been dominant in the industry. However, studies have pointed out that phthalates are a type of persistent organic pollutant that is not only reproductively toxic, but also causes deformities and cancer. The use of phthalate plasticizers is very risky, and the development and research of new, non-toxic, and environmentally friendly plasticizers has become the focus of attention. Cyclohexane 1,2-dicarboxylate, the product of selective hydrogenation of phthalates, is a non-toxic and environmentally friendly plasticizer, which will become the first choice to replace phthalates in the future plasticizer field.
[0003] CN114797924A discloses a Ni2P / SiC porous catalyst prepared by sol-gel and carbon thermal reduction reaction using pollen as a template. The catalyst has a large specific surface area and a strong loading capacity. In a fixed bed quartz tube reactor, the hydrogen pressure is 2-4MPa, the reaction temperature is 120-130°C, and the space velocity is 0.4-0.8h -1 Under the conditions of , the activity and selectivity of the catalyst both reached more than 99%, but the test data measured under the reaction conditions did not include the reaction time, so it was impossible to know whether the activity and selectivity of the catalyst decreased after being used for a period of time, and thus the stability of the catalyst was unknown.
[0004] CN113651694A discloses a supported diisononyl phthalate hydrogenation catalyst with Rh or Ru as active component and template-modified alumina as carrier. The catalyst has a hydrogen-ester ratio of 250, a reaction pressure of 6 MPa, a reaction temperature of 150°C, and a liquid space velocity of 0.6 h -1 Under the conditions, the DINP conversion rate is 90.2-100%, and the DINCH selectivity is 95.0-99.9%, but the loss rate of precious metals in the active components of the catalyst is not mentioned, and the stability of the catalyst cannot be determined.
[0005] CN111036194A discloses a method for preparing a catalyst for hydrogenation of phthalates, wherein at least one of Ru, Pd, Pt, Ag, Au, Ni and Rh is selected as an active component, and one of Al2O3, SiO2, ZrO2, TiO2, CeO2 and a molecular sieve is selected as a carrier. Under the conditions of a reaction temperature of 180°C, a reaction pressure of 8 MPa and a hydrogen-ester ratio of 50 in a fixed bed reactor, the loss rate of precious metals is low, the stability is good, and the conversion rate and selectivity of the catalyst both reach more than 99%. However, the value of the liquid space velocity is not mentioned in the reaction conditions, and it is unknown at what reaction load the stability data of the catalyst is measured.
[0006] CN106984310A discloses a method for preparing a phthalate hydrogenation catalyst, wherein the noble metal Ru is selected as an active component, the carrier is one of zirconium oxide, magnesium oxide, silicon oxide or aluminum oxide, and an intermittent hydrogenation process is adopted. The catalyst needs to be reduced for 3-10 hours at 100-300° C. in a hydrogen atmosphere, and the product yield is 99.49%. The reduction time is long, and the intermittent process has the disadvantages of not being able to produce continuously, having low product stability, and not being easy to detect online compared to the fixed bed reaction process.
[0007] At present, in the hydrogenation of phthalates, technicians in this field intend to prepare high-activity, high-selectivity and good-stability catalysts in a fixed-bed reaction process under relatively mild reaction conditions in order to achieve large-scale industrial applications; however, under these conditions, due to the high reaction pressure and temperature and the continuous passage of raw materials through the catalyst bed, the sintering and loss of precious metal active components are easily caused. Therefore, the selectivity and stability of the catalyst is an important issue that researchers need to solve. Summary of the invention
[0008] The purpose of the present invention is to overcome the problems in the prior art that in a fixed trickle bed reactor, the catalyst runs for a long time, the loss rate of the active component noble metal Ru is high, and the catalyst stability is poor. A catalyst for hydrogenation of phthalates, a preparation method and application thereof, and a method for preparing cyclohexane 1,2-diisononyl dicarboxylate from diisononyl phthalate are provided. The catalyst has high catalytic activity, high selectivity and good stability.
[0009] In order to achieve the above-mentioned object, the first aspect of the present invention provides a catalyst for hydrogenation of phthalates, the catalyst comprising: a primary catalyst precursor and Fe coated on the surface of the primary catalyst precursor; wherein the primary catalyst precursor comprises a carrier and Ru loaded on the surface of the carrier; wherein,
[0010] The carrier comprises a primary modified carrier and a modulation metal oxide loaded on the primary modified carrier; the primary modified carrier is a mixed metal oxide of Al and Ti.
[0011] The second aspect of the present invention provides a method for preparing a catalyst for hydrogenation of phthalates, the preparation method comprising the following steps:
[0012] (1) mixing boehmite and TiO2 and heat treating the mixture to obtain a primary modified carrier;
[0013] (2) mixing the primary modified support with an aqueous solution containing a modulating metal element, then neutralizing and precipitating with an alkali solution, and performing a first calcination on the obtained precipitate to obtain a secondary modified support;
[0014] (3) performing a first impregnation of the secondary modified support with a hydrazine hydrate solution containing the Ru element, and performing a second calcination on the obtained solid to obtain a primary catalyst precursor;
[0015] (4) The primary catalyst precursor is impregnated with a solution containing the Fe element for a second time, and the obtained solid is calcined for a third time and subjected to a reduction reaction to obtain the catalyst.
[0016] The third aspect of the present invention provides a catalyst for hydrogenation of phthalates prepared by the preparation method provided by the present invention.
[0017] A fourth aspect of the present invention provides a use of the catalyst for hydrogenation of phthalates provided by the present invention in catalyzing the hydrogenation reaction of phthalates to prepare cyclohexane 1,2-dicarboxylate.
[0018] A fifth aspect of the present invention provides a method for preparing diisononyl cyclohexane dicarboxylate from diisononyl phthalate, the method comprising: subjecting diisononyl phthalate to a hydrogenation reaction in a hydrogen atmosphere in the presence of a catalyst for hydrogenation of phthalates provided by the present invention;
[0019] The conditions of the hydrogenation reaction include: a molar ratio of diisononyl phthalate to H2 of 1:(40-160), a temperature of 145-155°C, a pressure of 5-7MPa, a time of 80-600h, and a liquid hourly space velocity of diisononyl phthalate of 0.5-0.7h -1 .
[0020] Through the above technical solution, the beneficial effects of the present invention are:
[0021] A primary modified carrier is obtained by heat treating boehmite and TiO2 with a good γ-AlOOH crystal form, so that the primary modified carrier has a suitable specific surface area and pore volume; subsequently, a secondary modified carrier is obtained by adjusting the specific metal oxide component. The carrier can have a good bonding degree with the precious metal active component Ru, so that the catalyst has a good structure-activity relationship, thereby improving the activity and stability of the catalyst.
[0022] In the catalyst of the present invention, Ru and Fe bimetallic are used as active components, wherein the active component Ru is evenly distributed on the carrier, and then the active component Fe forms a wrapping around the noble metal active component Ru, locally forming a bimetallic framework, and the Fe element not only wraps Ru therein, but also penetrates into the surface of the carrier that is not loaded by Ru, thereby combining with the carrier, playing the role of both active component and structure modifier, so that the noble metal Ru does not lose or loses very little after the catalyst is used for a long time, and has good stability. The catalyst for hydrogenation of phthalates prepared by the present invention is used in a trickle bed reactor, and has a short reduction time, a low hydrogen-ester ratio, a high catalyst activity, and good selectivity; after long-term operation, the active component Fe not only wraps the noble metal Ru, so that the noble metal Ru does not lose or loses very little, forming a stable structure-activity relationship, and the active component Fe and the noble metal Ru can also have a synergistic effect, which plays a role in enhancing the reaction activity. In the preparation of diisononyl cyclohexane dicarboxylate by hydrogenation of diisononyl phthalate using a catalyst, when the H2 / ester molar ratio is 150, after 100 hours of reaction and 500 hours of reaction, the DINP conversion rate is above 96%, the DINCH selectivity is above 95%, and the loss rate of the precious metal Ru does not exceed 0.04ppm%; when the H2 / ester molar ratio is 50, after 100 hours of reaction and 500 hours of reaction, the DINP conversion rate is above 96%, the DINCH selectivity is above 95%, and the loss rate of the precious metal Ru does not exceed 0.03ppm%.
[0023] In a preferred embodiment of the present invention, by selecting a suitable ratio of boehmite and TiO2, and heat treatment conditions, a multi-dimensional carrier architecture is formed with γ-Al2O3 as the main component and other crystal forms as the auxiliary components, so that the primary modified carrier obtains a more suitable specific surface area and pore volume; by selecting a suitable amount and type of tuning metal elements, the amount of Ru and Fe elements, the impregnation method and the three-time calcination conditions, the activity, selectivity and stability of the catalyst are further improved, and the precious metal Ru is not lost after use, and the amount of precious metal Ru is low, only 0.015-0.032% of the total mass of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is the XRD spectra of the finished catalyst products S1-S4 prepared in Examples 1-4 of the present invention.
[0025] Description of Reference Numerals
[0026] a XRD spectrum of finished catalyst S1 b XRD spectrum of finished catalyst S2
[0027] c XRD spectrum of finished catalyst S3 d XRD spectrum of finished catalyst S4 DETAILED DESCRIPTION
[0028] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0029] The first aspect of the present invention provides a catalyst for hydrogenation of phthalates, the catalyst comprising: a primary catalyst precursor and Fe coated on the surface of the primary catalyst precursor; wherein the primary catalyst precursor comprises a carrier and Ru loaded on the surface of the carrier; wherein,
[0030] The carrier comprises a primary modified carrier and a modulation metal oxide loaded on the primary modified carrier; the primary modified carrier is a mixed metal oxide of Al and Ti.
[0031] The primary modified carrier of the present invention is a mixed metal oxide of Al and Ti, so that the carrier precursor (primary modified carrier) can obtain a suitable specific surface area and pore volume; subsequently, the secondary modified carrier is obtained by adjusting the metal components. The bonding degree between such a carrier and the noble metal active component Ru makes the catalyst have a good structure-activity relationship, thereby improving the activity and stability of the catalyst.
[0032] The present invention adopts Ru and Fe bimetallic as active components, wherein the active component Ru is distributed on the carrier, and the active component Fe wraps the noble metal active component Ru to locally form a bimetallic structure. The Fe element not only wraps Ru therein, but also penetrates into the surface of the carrier that is not loaded with Ru, thereby combining with the carrier, playing the role of both active component and structure modifier, so that the noble metal Ru is not lost or lost very little after the catalyst is used for a long time, and the stability is good.
[0033] According to the present invention, preferably, the Ru element is uniformly loaded on the surface of the carrier.
[0034] According to the present invention, preferably, based on the total weight of the catalyst, the contents of Ru and Fe in the catalyst are 0.015-0.032 wt% and 0.1-0.2 wt%, respectively.
[0035] According to the present invention, preferably, the modulated metal oxide is selected from at least one of Zr oxide, Cu oxide, Mg oxide, K oxide, Na oxide and Ca oxide. The selection of these modulated metal oxides can make the carrier stability and surface acidity more suitable, so that the active substance Ru can be better and more evenly loaded on the carrier, so that the prepared catalyst has a higher selectivity for DINCH when catalyzing the hydrogenation reaction of phthalates, while other metal oxides cannot achieve these two effects at the same time.
[0036] According to the present invention, a portion of the modulated metal oxide is loaded on the surface of the primary modified support, and another portion is loaded inside the pores of the primary modified support.
[0037] According to the present invention, preferably, based on the total weight of the catalyst, the content of the modulating metal element in the carrier is 5.45-6.55wt%. The modulating metal element is the technical element corresponding to the modulating metal oxide contained in the catalyst. The content of the modulating metal element may also refer to the content of the modulating metal oxide in terms of the contained metal element. The content of the modulating metal element in the carrier satisfies this range, which can make the surface acidity of the carrier within the range of 0.2-0.4mmol / g, which is more suitable for the activity of such hydrogenation catalyst.
[0038] According to the present invention, preferably, based on the total weight of the catalyst, the content of the γ-Al2O3 crystal form in the primary modified carrier is 80-89wt%. The primary modified carrier is mainly composed of the γ-Al2O3 crystal form, and other crystal forms are supplemented, so that the primary modified carrier with such a crystal form ratio has a more suitable specific surface area and pore volume.
[0039] According to the present invention, preferably, based on the total weight of the catalyst, the contents of Al and Ti in the primary modified carrier are 44.26-48.21 wt% and 5.14-9.44 wt%, respectively.
[0040] In the present invention, the contents of Ru and Fe, the contents of Al and Ti, and the content of the modulating metal element can be measured by using an AA6300F atomic absorption spectrometer.
[0041] According to the present invention, preferably, based on the total weight of the catalyst, the content of the primary modified carrier is 93.22-94.44 wt%.
[0042] According to the present invention, preferably, the specific surface area of the catalyst is 200-230m 2 / g, pore volume is 0.2-0.3cm 3 / g, and the average pore size is 4.1-5.1nm.
[0043] In the present invention, the specific surface area, pore volume and average pore diameter of the catalyst can be measured by a low-temperature N2 adsorption-desorption method using a NOVA2200e physical adsorption instrument.
[0044] A second aspect of the present invention provides a method for preparing a catalyst for hydrogenation of phthalates, the preparation method comprising the following steps:
[0045] (1) Boehmite and TiO2 are mixed and heat treated to obtain a primary modified carrier.
[0046] (2) The primary modified carrier is mixed with an aqueous solution containing a modulation metal element, and then neutralized and precipitated with an alkali solution. The obtained precipitate is subjected to a first calcination to obtain a secondary modified carrier.
[0047] (3) The secondary modified carrier is first impregnated with a hydrazine hydrate solution containing the Ru element, and the obtained solid is second calcined to obtain a primary catalyst precursor.
[0048] (4) The primary catalyst precursor is impregnated with a solution containing the Fe element for a second time, and the obtained solid is calcined for a third time and subjected to a reduction reaction to obtain the catalyst.
[0049] The present invention obtains a primary modified carrier by heat-treating boehmite and TiO2 with good crystal forms, thereby forming a multi-dimensional carrier framework including various crystal forms such as γ-Al2O3, γ-Al-O-Ti, Al-O-Al, Ti-O-Ti, Al-OO-Al, Al-OO-Ti and O-Ti-O, so that the primary modified carrier obtains a suitable specific surface area and pore volume; subsequently, the metal component is adjusted to obtain a secondary modified carrier, and the degree of bonding between such a carrier and the noble metal active component Ru makes the catalyst have a good structure-activity relationship, so that the activity and stability of the catalyst can also be improved, and the Ru loss rate is low.
[0050] In step (2), the primary modified carrier is mixed with an aqueous solution containing a modulating metal element, and then neutralized and precipitated with an alkali solution. The obtained precipitate is subjected to a first roasting to obtain a secondary modified carrier. The primary modified carrier forms a metastable state, and then the modulating metal element is added. After neutralization and precipitation, the modulating metal element and the primary modified carrier can be fully and evenly mixed to form a stable mixture, so that a part of the modulating metal element is loaded inside the pores of the primary modified carrier, and a part is evenly loaded on the surface of the primary modified carrier. During the roasting process, the modulating metal element inside the pores and on the surface of the primary modified carrier is oxidized to a modulating metal oxide, thereby obtaining a secondary modified carrier.
[0051] The secondary modified carrier is first impregnated with a hydrazine hydrate solution containing the Ru element, and the Ru element is reduced under the action of hydrazine hydrate, and the Ru element is loaded on the surface of the secondary modified carrier in a reduced state, and then the Ru element loaded on the surface of the secondary modified carrier is slightly oxidized by the second roasting and has a higher degree of binding with the secondary modified carrier. After the Ru element is slightly oxidized, the Fe element can more easily obtain oxygen combined with the Ru element during the third roasting, so that the Ru element is in a critical reduced state. Ru and Fe need to catalyze the hydrogenation of phthalates in a reduced state. After the Fe element is combined with the Ru element, when the subsequent catalyst performs a reduction reaction, it is only necessary to ensure that the Fe element is fully reduced. The Fe element is coated on the surface of the primary catalyst precursor, and the Fe element not only wraps Ru therein, but also penetrates into the carrier surface that is not loaded by Ru, thereby combining with the carrier, playing both the role of active component and the role of structure modifier, so that the precious metal Ru is not lost or lost in very small amounts after the catalyst is used for a long time, and the stability is good.
[0052] Ru and Fe in the catalyst need to catalyze phthalate hydrogenation in a reduced state, so the product after the third calcination needs to be subjected to a reduction reaction to reduce Fe to a reduced state to form a phthalate hydrogenation catalyst. The reduction reaction can be completed when preparing the catalyst, or the influence of oxidation and deterioration of the catalyst during storage and transportation before use can be considered, and the reduction reaction can be carried out in situ in the reaction unit before the catalytic hydrogenation reaction. Those skilled in the art should not be construed as limiting the present invention.
[0053] In the preparation method of the catalyst for phthalate hydrogenation in the second aspect of the present invention, the types and compositions of the primary modified carrier, the secondary modified carrier and the primary catalyst precursor are exactly the same as the types and compositions of the primary modified carrier, the carrier and the primary catalyst precursor in the catalyst for phthalate hydrogenation described in the first aspect of the present invention. In order to avoid repetition, the present invention will not be described in detail in the second aspect, and those skilled in the art should not understand it as a limitation of the present invention.
[0054] According to the present invention, preferably, in step (1), the temperature of the heat treatment is 400-600°C and the time is 2-4 hours. When the heat treatment conditions meet this range, a multi-phase crystal structure dominated by γ-Al2O3 crystal structure can be better obtained, otherwise more other crystal structures are obtained and the requirements for activity and stability of the catalyst cannot be met.
[0055] According to the present invention, preferably, in step (1), boehmite is calculated as Al, TiO2 is calculated as Ti, and the molar ratio of boehmite:TiO2 is (8-16):1. Boehmite and TiO2 are mixed in this ratio and heat-treated according to the above conditions to form a primary modified carrier with a multi-dimensional carrier structure mainly composed of γ-Al2O3 crystal form and other crystal forms as auxiliary, so that the primary modified carrier has a more suitable specific surface area and pore volume, and a specific surface area of 228-250m 2 / g, pore volume is 0.29-0.41cm 3 / g, a primary modified carrier with an average pore size of 5.3-6.1nm.
[0056] According to the present invention, preferably, the heat treatment is performed in an air atmosphere.
[0057] According to the present invention, preferably, in step (2), the content of the modulating metal element in the aqueous solution is 0.02-0.1 mol / L. The content of the modulating metal element in the salt solution satisfies this range, which can better disperse the modulating metal element on the surface and inside the pores of the primary modified carrier, thereby enhancing the stability of the carrier structure.
[0058] According to the present invention, preferably, in step (2), the modulation metal element is selected from at least one of Zr, Cu, Mg, K, Na and Ca.
[0059] According to the present invention, preferably, the temperature of the neutralization precipitation is 45-60° C., and the pH value of the precipitate is 8-9.5.
[0060] According to the present invention, preferably, in step (2), the alkali solution is selected from sodium hydroxide and / or potassium hydroxide.
[0061] According to the present invention, preferably, in step (2), the obtained precipitate is first dried and then calcined; wherein the temperature of the first drying is 150-180°C and the time is 1.5-2.5 hours; the time is most preferably 2 hours. When the conditions of the first drying meet this range, the physical water contained in the carrier can be better removed to obtain a material with a suitable moisture content.
[0062] According to the present invention, preferably, the temperature of the first calcination is 500-600°C and the time is 2-4 hours. When the conditions of the first calcination meet this range, a secondary modified carrier with suitable specific surface area and pore structure can be better obtained.
[0063] According to the present invention, preferably, step (2) further comprises: tableting the product after the first calcination to obtain the secondary modified carrier.
[0064] According to the present invention, preferably, the content of hydrazine hydrate in the hydrazine hydrate solution containing the Ru element is 15-25wt%, most preferably 20wt%.
[0065] According to the present invention, preferably, in the Ru-containing hydrazine hydrate solution, the Ru element is derived from at least one of RuCl3, RuI3 and potassium chlororuthenate, preferably RuCl3; and the content of the Ru element is 3-6.4 mmol / L. Controlling the content of the Ru element in the Ru-containing solution within this range can enable the Ru element to have a suitable loading amount on the secondary modified carrier.
[0066] According to the present invention, preferably, the first impregnation is a supersaturated impregnation. By supersaturated impregnation, the secondary modified carrier is immersed in an excess of impregnation solution containing the Ru element, so that the volume of the impregnation solution exceeds the absorbable volume of the secondary modified carrier, so that the carrier finally reaches adsorption equilibrium. Supersaturated impregnation can make the impregnation solution containing the Ru element contact evenly with the secondary modified carrier, so that the active component Ru is evenly distributed on the secondary modified carrier, and the remaining impregnation solution can continue to be used in the subsequent preparation of the catalyst, without causing waste of precious metals.
[0067] According to the present invention, preferably, the temperature of the first impregnation is 25-40° C. and the time is 1.5-2.5 h. When the conditions of the first impregnation meet this range, more dispersed Ru elements with good reduction degree can be obtained.
[0068] According to the present invention, preferably, the first impregnation is performed at a stirring speed of 100-300 rpm.
[0069] According to the present invention, preferably, in step (3), the obtained solid is first subjected to a second drying and then to a second calcination; wherein the temperature of the second drying is 110-130°C and the time is 1.5-2.5 hours; the time is most preferably 2 hours. When the second drying conditions meet this range, the physical water contained in the primary catalyst precursor can be better removed to obtain a material that is convenient for the subsequent second calcination.
[0070] According to the present invention, preferably, the second calcination temperature is 300-400° C. and the time is 1-2 hours. When the second calcination conditions meet this range, the residual hydrazine hydrate solution can be effectively decomposed, so that the Ru element is better loaded on the carrier.
[0071] According to the present invention, preferably, the specific surface area of the primary catalyst precursor is 215-240m 2 / g, pore volume is 0.26-0.35cm 3 / g, and the average pore size is 4.3-5.3nm.
[0072] The specific surface area of the primary modified carrier without the modulated metal oxide on the surface and inside the pores is 228-250m 2 / g, pore volume is 0.29-0.41cm 3 / g, with an average pore size of 5.3-6.1nm; and the specific surface area of the primary catalyst precursor after loading the modulated metal oxide is 215-240m 2 / g, pore volume is 0.26-0.35cm 3 / g, and the average pore size is 4.3-5.3nm. This shows that the modulation of metal oxide plays a role in structural modulation.
[0073] According to the present invention, preferably, in step (4), the Fe element in the solution containing the Fe element is derived from at least one of Fe(NO3)2, FeSO4 and FeCl2, preferably Fe(NO3)2; the content of the Fe element in the solution containing the Fe element is 0.02-0.04 mol / L. When the content of the Fe element in the solution containing the Fe element meets this range, it can improve the activity of the catalyst and effectively stabilize the load of the Ru element on the carrier to prevent the loss of the precious metal Ru element.
[0074] According to the present invention, preferably, the second impregnation is a saturated impregnation. By saturated impregnation, the primary catalyst precursor is immersed in an impregnation solution containing the Fe element, so that the volume of the impregnation solution is equal to the absorbable volume of the primary catalyst precursor, so that the Fe element is coated on the surface of the primary catalyst precursor. The Fe load itself is relatively high and is wrapped in the outer layer. If an oversaturated impregnation is adopted, it will cause excessive Fe adsorption and thus affect the activity of Ru. The saturated impregnation can make Fe coated on the surface of the primary catalyst precursor in an appropriate amount.
[0075] According to the present invention, preferably, the temperature of the second impregnation is 30-50°C and the time is 1-2 hours. When the conditions of the second impregnation meet this range, the Fe element can be effectively dispersed in the solution and further react with the slightly oxidized Ru element to generate relatively stable Fe and Ru oxides.
[0076] According to the present invention, preferably, in step (4), the obtained solid is first subjected to a third drying and then to a third calcination; wherein the temperature of the third drying is 130-150°C and the time is 1.5-2.5 hours; the time is most preferably 2 hours. When the conditions of the third drying meet this range, the physical water contained in the secondary catalyst precursor can be better removed to obtain a material with a suitable moisture content.
[0077] According to the present invention, preferably, the temperature of the third calcination is 400-500° C. and the time is 2-4 hours. When the conditions of the third calcination meet this range, the nitrate ions, sulfate ions and chloride ions remaining on the surface of the primary catalyst precursor can be better decomposed, thereby not destroying the specific surface area of the catalyst precursor before the reduction reaction.
[0078] According to the present invention, preferably, the reduction reaction is carried out in a reducing atmosphere, for example, in a hydrogen atmosphere.
[0079] According to the present invention, preferably, the reduction reaction conditions include: temperature of 210-230° C., pressure of 0.3-0.8 MPa, and time of 0.5-1.5 h.
[0080] According to the present invention, preferably, the specific surface area of the catalyst is 200-230m 2 / g, pore volume is 0.2-0.3cm 3 / g, and the average pore size is 4.1-5.1nm.
[0081] The specific surface area of the primary catalyst precursor before Fe coating is 215-240m 2 / g, pore volume is 0.26-0.35cm 3 / g, with an average pore size of 4.3-5.3nm; the finished catalyst after Fe coating was crushed and the central part of the catalyst was taken for analysis, and the specific surface area inside the finished catalyst was found to be 200-230m 2 / g, pore volume is 0.2-0.3cm 3 / g, and the average pore size is 4.1-5.1nm. This shows that the Fe element not only wraps Ru into it, but also penetrates into the surface of the carrier that is not loaded with Ru, thereby combining with the carrier, playing the role of both active component and structure modifier.
[0082] In the present invention, the specific surface area, pore volume and average pore diameter of the primary modified carrier, the primary catalyst precursor and the catalyst can be measured by a low-temperature N2 adsorption-desorption method using a NOVA2200e physical adsorption instrument.
[0083] The third aspect of the present invention provides a catalyst for hydrogenation of phthalates prepared by the preparation method provided by the present invention.
[0084] The fourth aspect of the present invention provides an application of the phthalate hydrogenation catalyst provided by the present invention in catalyzing the hydrogenation reaction of phthalates to prepare cyclohexane 1,2-dicarboxylate, wherein the phthalate is preferably diisononyl phthalate (DINP), and the cyclohexane 1,2-dicarboxylate is diisononyl cyclohexane 1,2-dicarboxylate (DINCH).
[0085] A fifth aspect of the present invention provides a method for preparing diisononyl cyclohexane dicarboxylate from diisononyl phthalate, the method comprising: subjecting diisononyl phthalate to a hydrogenation reaction in a hydrogen atmosphere in the presence of a catalyst for hydrogenation of phthalates provided by the present invention;
[0086] The conditions of the hydrogenation reaction include: a molar ratio of diisononyl phthalate to H2 of 1:(40-160), a temperature of 145-155°C, a pressure of 5-7MPa, a time of 80-600h, and a liquid hourly space velocity of diisononyl phthalate of 0.5-0.7h -1 .
[0087] The present invention will be described in detail below through examples and comparative examples. In the following examples, unless otherwise specified, all conventional methods are used; the reagents and materials used, unless otherwise specified, can be obtained from commercial sources. The determination methods involved in each example and comparative example are as follows:
[0088] The specific surface area, pore volume and average pore diameter were determined by low-temperature N2 adsorption-desorption method using NOVA2200e physical adsorption instrument;
[0089] The content of γ-Al2O3 was determined by chemical titration;
[0090] The contents of Ru and Fe, Al and Ti, and the content of the modulating metal element were determined using an AA6300F atomic absorption spectrometer;
[0091] The content of the primary modified support was determined using a Thermo Scientific iCAP6300 plasma emission spectrometer;
[0092] The surface acidity of the carrier was determined by titration with adsorption indicator n-butylamine;
[0093] The loss rate of metal Ru was determined by microwave digestion ICP-MS.
[0094] The following examples are used to illustrate the preparation of catalysts for hydrogenation of phthalates.
[0095] Example 1
[0096] Step (1): In an air atmosphere, 102 g of boehmite and 10 g of TiO2 (Al:Ti molar ratio = 16:1) were uniformly mixed and heat treated in a muffle furnace at 400°C for 4 h to obtain a specific surface area of 250 m 2 / g, pore volume is 0.41cm 3 / g, a primary modified carrier with an average pore size of 6.1 nm;
[0097] Step (2): dissolving 10 g of copper nitrate trihydrate and 30 g of magnesium nitrate hexahydrate in water to prepare a 0.1 mol / L mixed metal salt solution, then adding the primary modified carrier to the mixed metal salt solution, and then neutralizing and precipitating with sodium hydroxide at 45° C., controlling the end point pH value to be 8, filtering the obtained material, drying at 150° C. for 2 h, calcining at 600° C. for 2 h and tableting to obtain a secondary modified carrier, whose surface acidity is 0.26 mmol / g;
[0098] Step (3): Dissolve RuCl3 in a 20 wt% hydrazine hydrate solution to prepare a 3 mmol / L solution rich in active component Ru 3+ The solution was stirred at 100 rpm and the temperature was 40°C. The secondary modified support was immersed in the solution for 1.5 h by supersaturated impregnation method, and then taken out and dried at 110°C for 2 h and calcined at 300°C for 2 h to obtain a surface area of 240 m 2 / g, pore volume is 0.35cm 3 / g, a primary catalyst precursor containing the active component Ru with an average pore size of 5.3nm;
[0099] Step (4): Dissolve Fe(NO3)2 in water to prepare 0.02 mol / L Fe(NO3)2 2+ The solution was controlled at 30°C, and the primary catalyst precursor was immersed in it by saturated impregnation for 1 hour, and then taken out and dried at 150°C for 2 hours and calcined at 500°C for 3 hours to obtain a catalyst precursor. In a hydrogen atmosphere, the catalyst precursor was reduced at 220°C and 0.5MPa hydrogen atmosphere for 1 hour, and finally a specific surface area of 230m 2 / g, pore volume is 0.3cm 3 / g, an average pore size of 5.1nm, and a dual-active metal component catalyst product S1 containing 0.1wt% Fe and 0.015wt% Ru; wherein,
[0100] Based on the total weight of the finished catalyst S1, the content of γ-Al2O3 crystal in the carrier is 89wt%, the content of Al element and Ti element in the primary modified carrier is 48.21wt% and 5.14wt% respectively, the content of the primary modified carrier is 94.44wt%, and the content of Cu element and Mg element is 2.64wt% and 2.81wt% respectively.
[0101] The XRD spectrum of the finished catalyst S1 is shown in Figure 1 ,Depend on Figure 1 It can be seen that the diffraction peaks at 47.8° and 67.2° are typical γ-Al2O3 diffraction peaks. There are no diffraction peaks of active metals Fe and Ru in the figure, indicating that the active metals Fe and Ru are highly dispersed on the carrier surface.
[0102] Example 2
[0103] Step (1): In an air atmosphere, 102 g of boehmite and 20 g of TiO2 (Al:Ti molar ratio = 8:1) were uniformly mixed and heat treated in a muffle furnace at 600°C for 2 h to obtain a specific surface area of 228 m 2 / g, pore volume is 0.29cm 3 / g, a primary modified carrier with an average pore size of 5.3 nm;
[0104] Step (2): 10 g potassium nitrate and 10 g zirconium nitrate are dissolved in water to prepare a 0.1 mol / L mixed metal salt solution, and then the primary modified carrier is added to the mixed metal salt solution, and then neutralized and precipitated with sodium hydroxide at 60° C., and the end point pH value is controlled to be 9. The obtained material is then filtered, dried at 180° C. for 2 h, calcined at 600° C. for 3 h, and pressed into tablets to obtain a secondary modified carrier, whose surface acidity is 0.4 mmol / g;
[0105] Step (3): Dissolve RuCl3 in a 20 wt% hydrazine hydrate solution to prepare a 6.4 mmol / L solution rich in active component Ru 3+ The solution was stirred at 300 rpm and the temperature was 25°C. The secondary modified support was immersed in the solution for 2.5 hours by supersaturated impregnation method. The support was then taken out and dried at 130°C for 2 hours and calcined at 400°C for 1 hour to obtain a surface area of 215 m 2 / g, pore volume is 0.26cm 3 / g, a primary catalyst precursor containing the active component Ru with an average pore size of 4.3nm;
[0106] Step (4): Dissolve Fe(NO3)2 in water to prepare 0.02 mol / L Fe(NO3)2 2+ The temperature of the solution was controlled at 50°C, and the first-stage catalyst precursor was immersed in it by saturated impregnation for 2 hours, and then taken out and dried at 130°C for 2 hours and calcined at 400°C for 4 hours to obtain a catalyst precursor. In a hydrogen atmosphere, the catalyst precursor was reduced at 220°C and 0.5MPa hydrogen atmosphere for 1 hour, and finally a catalyst with a specific surface area of 200m 2 / g, pore volume is 0.2cm 3 / g, an average pore size of 4.1nm, and a dual-active metal component catalyst product S2 containing 0.1wt% Fe and 0.032wt% Ru; wherein,
[0107] Based on the total weight of the finished catalyst S2, the content of γ-Al2O3 in the carrier is 80wt%, the contents of Al and Ti in the primary modified carrier are 44.26wt% and 9.44wt% respectively, the content of the primary modified carrier is 93.34wt%, and the contents of K and Zr are 3.87wt% and 2.68wt% respectively.
[0108] The XRD spectrum of the finished catalyst S2 is shown in Figure 1 Similar to the XRD spectrum of the finished catalyst S1, the diffraction peaks at 47.8° and 67.2° are typical γ-Al2O3 diffraction peaks. There are no diffraction peaks of active metals Fe and Ru in the figure, indicating that the active metals Fe and Ru are highly dispersed on the carrier surface.
[0109] Example 3
[0110] Step (1): In an air atmosphere, 102 g of boehmite and 15 g of TiO2 (Al:Ti molar ratio = 10.67:1) were uniformly mixed and heat treated in a muffle furnace at 500°C for 3 h to obtain a specific surface area of 239 m 2 / g, pore volume is 0.32cm 3 / g, a primary modified carrier with an average pore size of 5.6nm;
[0111] Step (2): 10 g potassium nitrate and 10 g calcium nitrate are dissolved in water to prepare a 0.08 mol / L mixed metal salt solution, and then the primary modified carrier is added to the mixed metal salt solution, and then neutralized and precipitated with sodium hydroxide at 50° C., and the end point pH value is controlled to be 9.5. The obtained material is then filtered, dried at 160° C. for 2 h, calcined at 500° C. for 3 h, and pressed into tablets to obtain a secondary modified carrier, whose surface acidity is 0.2 mmol / g;
[0112] Step (3): Dissolve RuCl3 in a 20 wt% hydrazine hydrate solution to prepare a 6 mmol / L solution rich in active component Ru 3+ The solution was stirred at 200 rpm and the temperature was 30°C. The secondary modified carrier was immersed in the solution for 2 hours by supersaturated impregnation method. The carrier was then taken out and dried at 120°C for 2 hours and calcined at 380°C for 1 hour to obtain a surface area of 227 m 2 / g, pore volume is 0.31cm 3 / g, a primary catalyst precursor containing the active component Ru with an average pore diameter of 4.7nm;
[0113] Step (4): Dissolve Fe(NO3)2 in water to prepare 0.04 mol / L Fe(NO3)2 2+The temperature of the solution was controlled at 40°C, and the first-stage catalyst precursor was immersed in it by saturated impregnation for 2 hours, and then taken out and dried at 140°C for 2 hours and calcined at 450°C for 4 hours to obtain a catalyst precursor. In a hydrogen atmosphere, the catalyst precursor was reduced at 220°C and 0.5MPa hydrogen atmosphere for 1 hour, and finally a specific surface area of 216m 2 / g, pore volume is 0.25cm 3 / g, an average pore size of 4.5nm, and a dual-active metal component catalyst product S3 containing 0.2wt% Fe and 0.03wt% Ru; wherein,
[0114] Based on the total weight of the finished catalyst S3, the content of γ-Al2O3 in the carrier is 84.5wt%, the contents of Al and Ti in the primary modified carrier are 46.15wt% and 7.38wt% respectively, the content of the primary modified carrier is 93.47wt%, and the contents of K and Ca are 3.86wt% and 2.44wt% respectively.
[0115] The XRD spectrum of the finished catalyst S3 is shown in Figure 1 Similar to the XRD spectrum of the finished catalyst S1, the diffraction peaks at 47.8° and 67.2° are typical γ-Al2O3 diffraction peaks. There are no diffraction peaks of active metals Fe and Ru in the figure, indicating that the active metals Fe and Ru are highly dispersed on the carrier surface.
[0116] Example 4
[0117] Step (1): In an air atmosphere, 102 g of boehmite and 12.3 g of TiO2 (Al:Ti molar ratio = 13:1) were uniformly mixed and heat treated in a muffle furnace at 500°C for 3 h to obtain a specific surface area of 245 m 2 / g, pore volume is 0.38cm 3 / g, a primary modified carrier with an average pore size of 5.9 nm;
[0118] Step (2): 5 g of magnesium nitrate hexahydrate, 10 g of zirconium nitrate and 10 g of sodium nitrate are dissolved in water to prepare a 0.07 mol / L mixed metal salt solution, and then the primary modified carrier is added to the mixed metal salt solution, and then neutralized and precipitated with sodium hydroxide at 55° C., and the end point pH value is controlled to be 9. The obtained material is then filtered, dried at 180° C. for 2 h, calcined at 550° C. for 2 h and pressed into tablets to obtain a secondary modified carrier, whose surface acidity is 0.29 mmol / g;
[0119] Step (3): Dissolve RuCl3 in a 20 wt% hydrazine hydrate solution to prepare a 4 mmol / L solution rich in active component Ru 3+The solution was stirred at 150 rpm and the temperature was 30 °C. The secondary modified carrier was immersed in the solution for 2 h by supersaturated impregnation method. The carrier was then taken out and dried at 125 °C for 2 h and calcined at 400 °C for 1 h to obtain a specific surface area of 238 m 2 / g, pore volume is 0.32cm 3 / g, a primary catalyst precursor containing the active component Ru with an average pore size of 5.1nm;
[0120] Step (4): Dissolve Fe(NO3)2 in water to prepare 0.03 mol / L of Fe(NO3)2 2+ The solution was controlled at 30°C, and the primary catalyst precursor was immersed in it by saturated impregnation for 1 hour, and then taken out and dried at 150°C for 2 hours and calcined at 400°C for 4 hours to obtain a catalyst precursor. In a hydrogen atmosphere, the catalyst precursor was reduced at 220°C and 0.5MPa hydrogen atmosphere for 1 hour, and finally a specific surface area of 227m 2 / g, pore volume is 0.28cm 3 / g, an average pore size of 4.8nm, and a dual-active metal component catalyst product S4 containing 0.15wt% Fe and 0.02wt% Ru; wherein,
[0121] Based on the total weight of the finished catalyst S4, the content of γ-Al2O3 in the carrier is 86.9wt%, the contents of Al and Ti in the primary modified carrier are 47.24wt% and 6.2wt% respectively, the content of the primary modified carrier is 93.86wt%, and the contents of Mg, Zr and Na are 0.47wt%, 2.68wt% and 2.82wt% respectively.
[0122] The XRD spectrum of the finished catalyst S4 is shown in Figure 1 Similar to the XRD spectrum of the finished catalyst S1, the diffraction peaks at 47.8° and 67.2° are typical γ-Al2O3 diffraction peaks. There are no diffraction peaks of active metals Fe and Ru in the figure, indicating that the active metals Fe and Ru are highly dispersed on the carrier surface.
[0123] Example 5
[0124] The catalyst for hydrogenation of phthalates was prepared according to the method of Example 1, except that the ratio of boehmite to TiO2 was different. Specifically, in step (1), when preparing the primary modified carrier, 102 g of boehmite and 8.33 g of TiO2 (Al:Ti molar ratio = 19.21:1) were uniformly mixed and then heat treated to obtain a catalyst with a specific surface area of 278 m 2 / g, pore volume is 0.51cm 3 / g, the average pore size of the primary modified carrier is 6.8nm. The surface acidity of the secondary modified carrier is 0.26mmol / g, and then the specific surface area is 265m 2 / g, pore volume is 0.46cm 3 / g, and the average pore size of the primary catalyst precursor is 6.1nm. The final specific surface area is 257m 2 / g, pore volume is 0.39cm 3 / g, an average pore size of 5.8nm, and a dual-active metal component catalyst product S5 containing 0.11wt% Fe and 0.016wt% Ru; wherein,
[0125] Based on the total weight of the finished catalyst S5, the content of γ-Al2O3 in the carrier is 90.7wt%, the contents of Al and Ti in the primary modified carrier are 48.94wt% and 4.35wt% respectively, the content of the primary modified carrier is 94.42wt%, and the contents of Cu and Mg are 2.65wt% and 2.82wt% respectively.
[0126] Example 6
[0127] A catalyst for hydrogenation of phthalates was prepared according to the method of Example 1, except that in step (1), the heat treatment temperature was 750° C. and the time was 2 h, and a specific surface area of 320 m 2 / g, pore volume is 0.6cm 3 / g, the average pore size of the primary modified carrier is 7.5nm. The surface acidity of the secondary modified carrier is 0.26mmol / g, and then the specific surface area is 301m 2 / g, pore volume is 0.55cm 3 / g, and the average pore size of the primary catalyst precursor is 6.9nm. The final specific surface area is 286m 2 / g, pore volume is 0.43cm 3 / g, an average pore size of 6.2nm, and a dual-active metal component catalyst product S6 containing 0.11wt% Fe and 0.018wt% Ru; wherein,
[0128] Based on the total weight of the finished catalyst S6, the content of γ-Al2O3 in the carrier is 53.8wt%, the contents of Al and Ti in the primary modified carrier are 48.21wt% and 5.14wt% respectively, the content of the primary modified carrier is 94.42wt%, and the contents of Cu and Mg are 2.64wt% and 2.81wt% respectively.
[0129] Example 7
[0130] The catalyst for hydrogenation of phthalates was prepared according to the method of Example 1, except that the amount of the modulating metal element was different. Specifically, in step (2), 20 g of copper nitrate trihydrate and 60 g of magnesium nitrate hexahydrate were dissolved in water to prepare a 0.2 mol / L mixed metal salt solution, and then the primary modified carrier was added to the mixed metal salt solution. The surface acidity of the obtained secondary modified carrier was 0.16 mmol / g, and then the specific surface area was 219 m 2 / g, pore volume is 0.28cm 3 / g, and the average pore size of the primary catalyst precursor is 4.5nm. The final specific surface area is 208m 2 / g, pore volume is 0.2cm 3 / g, an average pore size of 4nm, and a dual-active metal component catalyst product S7 containing 0.09wt% Fe and 0.015wt% Ru; wherein,
[0131] Based on the total weight of the finished catalyst S7, the content of γ-Al2O3 in the carrier is 89wt%, the contents of Al and Ti in the primary modified carrier are 48.21wt% and 5.14wt% respectively, the content of the primary modified carrier is 89.58wt%, and the contents of Cu and Mg are 5.08wt% and 5.23wt% respectively.
[0132] Example 8
[0133] The catalyst for hydrogenation of phthalates was prepared according to the method of Example 1, except that the type of the modulating metal element was different. Specifically, in step (2), 12 g of lanthanum nitrate was dissolved in water to prepare a 0.1 mol / L mixed metal salt solution, and then the primary modified support was added to the mixed metal salt solution. The surface acidity of the obtained secondary modified support was 0.42 mmol / g, and then a specific surface area of 225 m 2 / g, pore volume is 0.26cm 3 / g, and the average pore size of the primary catalyst precursor is 4.5nm. The final specific surface area is 215m 2 / g, pore volume is 0.19cm 3 / g, an average pore size of 3.9nm, and a dual-active metal component catalyst product S8 containing 0.1wt% Fe and 0.016wt% Ru; wherein,
[0134] Based on the total weight of the finished catalyst S8, the content of γ-Al2O3 in the carrier is 89wt%, the contents of Al and Ti in the primary modified carrier are 48.21wt% and 5.14wt% respectively, the content of the primary modified carrier is 93.81wt%, and the content of lanthanum is 6.07wt%.
[0135] Example 9
[0136] The catalyst for hydrogenation of phthalates was prepared according to the method of Example 1, except that the conditions of the first calcination were different. Specifically, in step (2), the obtained material was filtered, dried, calcined at 400°C for 5h and pressed into tablets to obtain a secondary modified carrier with a surface acidity of 0.26mmol / g. Then, a catalyst with a specific surface area of 230m 2 / g, pore volume is 0.31cm 3 / g, and the average pore size of the primary catalyst precursor is 4.8nm. The final specific surface area is 219m 2 / g, pore volume is 0.26cm 3 / g, an average pore size of 4.3nm, and a double-layer active metal component catalyst product S9 containing 0.1wt% Fe and 0.015wt% Ru; wherein,
[0137] Based on the total weight of the finished catalyst S9, the content of γ-Al2O3 in the carrier is 89wt%, the contents of Al and Ti in the primary modified carrier are 48.21wt% and 5.14wt% respectively, the content of the primary modified carrier is 94.51wt%, and the contents of Cu and Mg are 2.61wt% and 2.76wt% respectively.
[0138] Example 10
[0139] The catalyst for hydrogenation of phthalates was prepared according to the method of Example 1, except that the sources of Ru and Fe were different. Specifically, in step (3), potassium chlororuthenate was dissolved in a 20 wt% hydrazine hydrate solution to prepare a 3 mmol / L active component Ru-rich solution. 3+ The specific surface area of the solution was 225 m 2 / g, pore volume is 0.34cm 3 / g, the average pore size of the primary catalyst precursor is 5.1nm. In step (4), FeSO4 is dissolved in water to prepare 0.02mol / L of active component Fe 2+ The final specific surface area is 220m 2 / g, pore volume is 0.28cm 3 / g, an average pore size of 4.6nm, and a double-layer active metal component catalyst product S10 containing 0.1wt% Fe and 0.015wt% Ru; wherein,
[0140] Based on the total weight of the finished catalyst S10, the content of γ-Al2O3 crystal in the carrier is 89wt%, the contents of Al and Ti in the primary modified carrier are 48.21wt% and 5.14wt% respectively, the content of the primary modified carrier is 94.43wt%, and the contents of Cu and Mg are 2.64wt% and 2.81wt% respectively.
[0141] Embodiment 11
[0142] The catalyst for hydrogenation of phthalates was prepared according to the method of Example 1, except that in step (3), 7 mmol / L of active component Ru was prepared. 3+ The specific surface area of the solution was 235m 2 / g, pore volume is 0.32cm 3 / g, and the average pore size of the primary catalyst precursor is 5nm. The final specific surface area is 227m 2 / g, pore volume is 0.28cm 3 / g, an average pore size of 4.7nm, and a double-layer active metal component catalyst product S11 containing 0.1wt% Fe and 0.035wt% Ru; wherein,
[0143] Based on the total weight of the finished catalyst S11, the content of γ-Al2O3 crystal in the carrier is 89wt%, the contents of Al and Ti in the primary modified carrier are 48.21wt% and 5.14wt% respectively, the content of the primary modified carrier is 94.41wt%, and the contents of Cu and Mg are 2.64wt% and 2.81wt% respectively.
[0144] Example 12
[0145] The catalyst for phthalate hydrogenation was prepared according to the method of Example 1, except that the conditions for the second calcination were different. Specifically, in step (3), the secondary modified support was impregnated with Ru-containing 3+ The solution was taken out and dried, and then calcined at 500℃ for 2h to obtain a specific surface area of 215m 2 / g, pore volume is 0.25cm 3 / g, and the average pore size is 4.4nm. The final specific surface area is 202m 2 / g, pore volume is 0.24cm 3 / g, an average pore size of 4.3nm, and a double-layer active metal component catalyst product S12 containing 0.1wt% Fe and 0.015wt% Ru; wherein,
[0146] Based on the total weight of the finished catalyst S12, the content of γ-Al2O3 crystal in the carrier is 89wt%, the content of Al element and Ti element in the primary modified carrier is 48.21wt% and 5.14wt% respectively, the content of the primary modified carrier is 94.47wt%, and the content of Cu element and Mg element is 2.64wt% and 2.81wt% respectively.
[0147] Embodiment 13
[0148] The catalyst for phthalate hydrogenation was prepared according to the method of Example 1, except that in step (4), Fe(NO3)2 was dissolved in water to prepare 0.05 mol / L Fe(NO3)2. 2+ The final specific surface area is 219m 2 / g, pore volume is 0.26cm 3 / g, an average pore size of 4.5nm, and a double-layer active metal component catalyst product S13 containing 0.25wt% Fe and 0.015wt% Ru; wherein,
[0149] Based on the total weight of the finished catalyst S13, the content of γ-Al2O3 crystal in the carrier is 89wt%, the content of Al element and Ti element in the primary modified carrier is 48.21wt% and 5.14wt% respectively, the content of the primary modified carrier is 94.31wt%, and the content of Cu element and Mg element is 2.63wt% and 2.79wt% respectively.
[0150] Embodiment 14
[0151] The catalyst for phthalate hydrogenation was prepared according to the method of Example 1, except that the conditions of the third calcination were different. Specifically, in step (4), the primary catalyst precursor was impregnated with Fe-containing 2+ The solution was taken out and dried, and then calcined at 600℃ for 2h to obtain a specific surface area of 228m 2 / g, pore volume is 0.26cm 3 / g, an average pore size of 4.6nm, and a double-layer active metal component catalyst product S14 containing 0.1wt% Fe and 0.015wt% Ru; wherein,
[0152] Based on the total weight of the finished catalyst S14, the content of γ-Al2O3 crystal in the carrier is 89wt%, the content of Al element and Ti element in the primary modified carrier is 48.21wt% and 5.14wt% respectively, the content of the primary modified carrier is 94.43wt%, and the content of Cu element and Mg element is 2.64wt% and 2.81wt% respectively.
[0153] Comparative Example 1
[0154] The catalyst carrier of this comparative example is γ-Al2O3 after heat treatment without modification, and Ru 3+ The element is dissolved in water instead of hydrazine hydrate. The preparation method of the catalyst is as follows:
[0155] RuCl3 was dissolved in water to obtain 3.6mmol / L of active component Ru 3+ Then 100 g of γ-Al2O3 carrier powder was heat treated at 60 °C for 2 h and pressed into tablets to obtain a specific surface area of 238 m 2 / g, pore volume is 0.41cm 3 / g, and the average pore size of the carrier is 5.7nm, and then an equal volume of it is immersed in the above-mentioned Ru salt solution for 2h; it is taken out and dried at 130℃ for 2h and calcined at 500℃ for 2h to obtain a primary catalyst precursor containing the active component Ru; Fe(NO3)2 is dissolved in water to prepare 0.02mol / L rich in active component Fe 2+ The first-stage catalyst precursor was immersed in the solution, which was taken out and dried at 130°C for 2h and calcined at 550°C for 1h to obtain a catalyst precursor. In a hydrogen atmosphere, the catalyst precursor was reduced at 220°C and 0.5MPa hydrogen atmosphere for 1h, and finally a specific surface area of 203m 2 / g, pore volume is 0.22cm 3 / g, an average pore diameter of 3.5nm, and a catalyst product D1 containing a bimetallic active component of 0.1wt% Fe and 0.018wt% Ru.
[0156] Comparative Example 2
[0157] The catalyst carrier of this comparative example is activated carbon after heat treatment, without loading the modulating metal element, and the loaded active metal component is only Ru. The preparation method of the catalyst is as follows:
[0158] RuCl3 was dissolved in 20 wt% hydrazine hydrate to obtain 6 mmol / L of active component Ru 3+ solution; 100 g of activated carbon was heat treated in a muffle furnace at 550 ° C for 3 h under air atmosphere; then the heat-treated activated carbon carrier (specific surface area of 950 m 2 / g, pore volume is 0.8cm 3 / g, average pore size 9.5nm) added Ru 3+ The catalyst precursor was immersed in the solution for 3 hours, then taken out and dried at 140°C for 2 hours and calcined at 500°C for 3 hours to obtain a catalyst precursor. In a hydrogen atmosphere, the catalyst precursor was reduced at 220°C and 0.5MPa hydrogen atmosphere for 1 hour, and finally a specific surface area of 582m 2 / g, pore volume is 0.68cm 3 / g, an average pore diameter of 7.2nm, and a catalyst product D2 containing 0.03wt% of Ru.
[0159] Comparative Example 3
[0160] The catalyst carrier of this comparative example is prepared by mixing heat-treated boehmite and cellulose, without loading the modulating metal element, and the loaded active metal components are Ru and Ni. The preparation method of the catalyst is as follows:
[0161] In air atmosphere, 102 g of boehmite was heat treated in a muffle furnace at 550 ° C for 3 h, and the heat-treated material was mixed with 3 g of cellulose and pressed into tablets to obtain a specific surface area of 278 m 2 / g, pore volume is 0.56m 3 / g, a carrier with an average pore size of 7.2 nm; RuCl3 was dissolved in a 20wt% hydrazine hydrate solution to prepare a 3.6mmol / L active component rich Ru 3+ The solution was sprayed on the carrier by atomization spraying method, and then dried at 120℃ for 2h and calcined at 400℃ for 2h to obtain a primary catalyst precursor containing the active component Ru; Ni(NO3)2 was dissolved in water to prepare 0.02mol / L Ni(NO3)2 2+ The temperature of the solution was controlled at 40°C, and the first-stage catalyst precursor was immersed in it by saturated impregnation for 1 hour. After it was taken out, it was dried at 140°C for 2 hours and calcined at 550°C for 3 hours to obtain a catalyst precursor. In a hydrogen atmosphere, the catalyst precursor was reduced at 220°C and 0.5MPa hydrogen atmosphere for 1 hour, and finally a specific surface area of 232m 2 / g, pore volume is 0.29cm 3 / g, an average pore diameter of 4.9nm, and a double-layer active metal component catalyst product D3 containing 0.1wt% Ni and 0.018wt% Ru.
[0162] Comparative Example 4
[0163] The catalyst carrier of this comparative example is prepared by mixing heat-treated TiO2 and cellulose, without loading the modulating metal element, and the loaded active metal component is only Ru. The preparation method of the catalyst is as follows:
[0164] RuCl3 was dissolved in a 20 wt% hydrazine hydrate solution to prepare a 5 mmol / L solution rich in active component Ru. 3+ In an air atmosphere, 100 g of TiO2 was heat treated in a muffle furnace at 550 ° C for 3 h, and then the heat-treated TiO2 carrier was kneaded and pressed with 3 g of cellulose to obtain a specific surface area of 201 m 2 / g, pore volume is 0.38cm 3 / g, the average pore size of the carrier is 5.2nm; the carrier is added with Ru 3+ The catalyst precursor was immersed in the solution for 2 hours; then it was taken out and dried at 130°C for 3 hours and calcined at 400°C for 4 hours to obtain a catalyst precursor. In a hydrogen atmosphere, the catalyst precursor was reduced at 220°C and 0.5MPa hydrogen atmosphere for 1 hour, and finally a specific surface area of 196m 2 / g, pore volume is 0.32cm 3 / g, an average pore diameter of 4.8nm, and a catalyst product D4 containing 0.025wt% of Ru.
[0165] Comparative Example 5
[0166] The catalyst carrier of this comparative example is prepared by mixing alumina and cellulose and calcining them, and does not load the modulating metal element, and the loaded active metal component is only Ru. The preparation method of the catalyst is as follows:
[0167] 102g of alumina powder and 3g of cellulose were uniformly mixed and pressed into tablets, then dried at 130℃ for 3h and calcined at 550℃ for 4h to obtain a specific surface area of 235m 2 / g, pore volume is 0.53cm 3 / g, a carrier with an average pore size of 5.6 nm; RuCl3 was dissolved in a 20wt% hydrazine hydrate solution to prepare a 3.6mmol / L active component rich Ru 3+ The solution was sprayed on the carrier by atomization spraying method, and then dried at 120℃ for 2h, and then calcined at 400℃ for 2h to obtain a catalyst precursor. In a hydrogen atmosphere, the catalyst precursor was reduced at 220℃ and 0.5MPa hydrogen atmosphere for 1h to obtain a specific surface area of 217m 2 / g, pore volume is 0.42cm 3 / g, an average pore diameter of 4.6nm, and a catalyst product D5 containing 0.018wt% of Ru.
[0168] Comparative Example 6
[0169] The catalyst carrier of this comparative example is prepared by mixing aluminum oxide and n-butylamine and calcining them, and does not load the modulating metal element, and the loaded active metal component is only Ru. The preparation method of the catalyst is as follows:
[0170] 102g of alumina powder and 5g of n-butylamine were uniformly mixed and extruded, then dried at 130℃ for 3h and calcined at 550℃ for 4h to obtain a specific surface area of 230m 2 / g, pore volume is 0.53cm 3 / g, the average pore size of the carrier is 5.2nm; RuCl3 is dissolved in water to prepare 0.18mol / L rich in active component Ru 3+ The solution was sprayed on the carrier by atomization spraying method, and then dried at 120℃ for 2h, and then calcined at 400℃ for 2h to obtain a catalyst precursor. In a hydrogen atmosphere, the catalyst precursor was reduced at 220℃ and 0.5MPa hydrogen atmosphere for 1h to obtain a specific surface area of 205m 2 / g, pore volume is 0.35cm 3 / g, an average pore diameter of 4.2nm, and a catalyst product D6 containing 0.9wt% of Ru.
[0171] Test Case
[0172] The catalysts prepared in each embodiment and comparative example were loaded into a fixed trickle bed reactor to catalyze the hydrogenation reaction of diisononyl phthalate to prepare diisononyl cyclohexane 1,2-dicarboxylate. In the presence of the catalyst, diisononyl phthalate was subjected to a hydrogenation reaction at a H2 / ester molar ratio of 150 and 50, a temperature of 150°C, a hydrogen pressure of 6 MPa, and a liquid space velocity of 0.6 h -1 The hydrogenation reaction was carried out under the conditions of , and samples were taken for analysis at 100h and 500h of hydrogenation reaction time. The results are shown in Table 1.
[0173] Table 1
[0174]
[0175] Table 1 (Continued Table 1)
[0176]
[0177]
[0178] It can be seen from the data in the embodiments, comparative examples and Table 1 that in Examples 1-14, the specific surface area, pore volume and average pore size of the primary catalyst precursor after the surface and pores are loaded with the modulated metal oxide are reduced to varying degrees compared with the primary modified carrier without the modulated metal oxide, indicating that the modulated metal oxide plays a role in structural modulation; the specific surface area, pore volume and average pore size of the finished catalyst after Fe coating are also reduced to varying degrees compared with the primary catalyst precursor without Fe coating on the surface, indicating that the Fe element not only serves as an active component but also plays a role in structural modulation.
[0179] In addition, the catalysts S1-S4 prepared by the method were subjected to the conditions of reaction temperature of 150°C, reaction pressure of 6MPa, and liquid space velocity of 0.6h -1Under the conditions, whether the H2 / ester molar ratio is 150 or 50, 100h and 500h all show good DINP conversion and DINCH selectivity, and good stability. Although catalysts S5-S14 are prepared by the method provided by the present invention, their preparation method does not meet the preferred conditions, so the activity and stability of the catalysts are slightly lower than S1-S4, but whether the H2 / ester molar ratio is 150 or 50, the DINP conversion and DINCH selectivity of 500h are not much fluctuated compared with 100h, and the stability is good. The conversion rate and selectivity of catalyst D1 prepared in comparative example 1 are generally average in the initial and later stages of the reaction, which may be caused by the fact that the Ru element is not pre-reduced during the preparation process and the reduction time is insufficient in the later stage. Although catalysts D2-D6 prepared in comparative examples 2-6 all show good conversion and selectivity in the initial stage of the reaction, their conversion rate and selectivity are significantly reduced after 500h of reaction, poor stability, and serious loss of metal Ru. To this end, after the reaction, the used catalysts S1-S14 and catalysts D1-D6 were subjected to physical and chemical analysis. The results showed that among the catalysts S1-S14 prepared by the method of the present invention, except for S5, S6, S7, and S11, which had a slight loss of precious metal Ru after use, there was no loss of precious metal Ru in other catalysts, and the precious metal loss rate of catalysts D1-D6 was 0.2-0.8ppm%.
[0180] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A catalyst for hydrogenation of phthalates, characterized in that: The catalyst comprises: a primary catalyst precursor and Fe coated on the surface of the primary catalyst precursor; wherein the primary catalyst precursor comprises a carrier and Ru loaded on the surface of the carrier; wherein, The carrier comprises a primary modified carrier and a modulation metal oxide loaded on the primary modified carrier; the primary modified carrier is a mixed metal oxide of Al and Ti.
2. The catalyst according to claim 1, characterized in that Based on the total weight of the catalyst, the contents of Ru and Fe in the catalyst are 0.015-0.032 wt% and 0.1-0.2 wt% respectively; Preferably, the modulation metal oxide is selected from at least one of Zr oxide, Cu oxide, Mg oxide, K oxide, Na oxide and Ca oxide.
3. The catalyst according to claim 1 or 2, characterized in that Based on the total weight of the catalyst, the content of the modulation metal element in the carrier is 5.45-6.55wt%; Preferably, based on the total weight of the catalyst, the content of γ-Al2O3 crystal in the primary modified carrier is 80-89wt%; Preferably, based on the total weight of the catalyst, the contents of Al and Ti in the primary modified carrier are 44.26-48.21 wt% and 5.14-9.44 wt% respectively; Preferably, based on the total weight of the catalyst, the content of the primary modified carrier is 93.22-94.44 wt %; Preferably, the specific surface area of the catalyst is 200-230m 2 / g, pore volume is 0.2-0.3cm 3 / g, and the average pore size is 4.1-5.1nm.
4. A method for preparing a catalyst for hydrogenation of phthalates, characterized in that: The preparation method comprises the following steps: (1) mixing boehmite and TiO2 and heat treating the mixture to obtain a primary modified carrier; (2) mixing the primary modified support with an aqueous solution containing a modulating metal element, then neutralizing and precipitating with an alkali solution, and performing a first calcination on the obtained precipitate to obtain a secondary modified support; (3) performing a first impregnation of the secondary modified support with a hydrazine hydrate solution containing the Ru element, and performing a second calcination on the obtained solid to obtain a primary catalyst precursor; (4) The primary catalyst precursor is impregnated with a solution containing the Fe element for a second time, and the obtained solid is calcined for a third time and subjected to a reduction reaction to obtain the catalyst.
5. The preparation method according to claim 4, characterized in that: In step (1), the heat treatment temperature is 400-600°C and the time is 2-4h; Preferably, in step (1), boehmite is calculated as Al, TiO2 is calculated as Ti, and the molar ratio of boehmite:TiO2 is (8-16):1; Preferably, the heat treatment is performed in an air atmosphere.
6. The preparation method according to claim 4 or 5, characterized in that: In step (2), the content of the modulating metal element in the aqueous solution is 0.02-0.1 mol / L; Preferably, the modulation metal element is selected from at least one of Zr, Cu, Mg, K, Na and Ca; Preferably, the temperature of the neutralization precipitation is 45-60° C., and the pH value of the precipitate is 8-9.5; Preferably, the first calcination is carried out at a temperature of 500-600° C. and for a time of 2-4 hours.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The Ru-containing hydrazine hydrate solution has a Ru content of 3-6.4 mmol / L; Preferably, the first impregnation is a supersaturated impregnation; Preferably, the temperature of the first impregnation is 25-40°C and the time is 1.5-2.5h; Preferably, the second calcination is carried out at a temperature of 300-400° C. and for a time of 1-2 h.
8. The preparation method according to any one of claims 4 to 7, characterized in that: In step (4), the content of Fe in the solution containing Fe is 0.02-0.04 mol / L; Preferably, the second impregnation is a saturation impregnation; Preferably, the temperature of the second impregnation is 30-50°C and the time is 1-2h; Preferably, the third calcination temperature is 400-500°C and the time is 2-4h; Preferably, the reduction reaction is carried out in a hydrogen atmosphere; Preferably, the reduction reaction conditions include: temperature of 210-230° C., pressure of 0.3-0.8 MPa, and time of 0.5-1.5 h.
9. A catalyst for hydrogenation of phthalate obtained by the preparation method according to any one of claims 4 to 8.
10. Use of the catalyst for hydrogenation of phthalate according to any one of claims 1 to 3 and 9 in catalyzing the hydrogenation reaction of phthalate to prepare cyclohexane 1,2-dicarboxylate.
11. A method for preparing diisononyl cyclohexane dicarboxylate from diisononyl phthalate, characterized in that: The method comprises: in the presence of the catalyst for hydrogenation of phthalates as claimed in any one of claims 1 to 3 and 9, subjecting diisononyl phthalate to a hydrogenation reaction in a hydrogen atmosphere; The conditions of the hydrogenation reaction include: a molar ratio of diisononyl phthalate to H2 of 1:(40-160), a temperature of 145-155°C, a pressure of 5-7MPa, a time of 80-600h, and a liquid hourly space velocity of diisononyl phthalate of 0.5-0.7h -1 .
Citation Information
Patent Citations
Preparation method of catalyst for phthalate hydrogenation
CN110624537A
Catalyst for preparing dimethyl 1,4-cyclohexanedicarboxylate through selective hydrogenation of dimethyl terephthalate and preparation method
CN111468112A
Preparation method of phthalate hydrogenation catalyst
CN116139876A
Method And Apparatus for Monitoring Violation of Exclusive Bus Lanes Based on V2I Communications
KR1020230013404A
